Analisa Aktor dalam Aktivitas Penambangan Timah Ilegal di Kabupaten Belitung Timur - Ristiandy, Risky; Purnomo, Eko Priyo (Jurnal PolGov, 2023)
This paper seeks to analyze actors and their roles in the relationship between actors in illegal tin mining activities in East Belitung Regency. This is done because actors who have been known to be the main actors among miners and rarely revealed other actors who cause this illegal activity to continue to operate In addition, this article also attempts to see how actors and their networks work and cause the problem of illegal tin mining in East Belitung Regency to occur and not be resolved until now. The approach used in this paper is a qualitative approach, using the Stake Holder Analysis method and interactive analysis methods conducted by researchers in the period of June 2022-January 2023. The analysis that can be seen from the results of the researchers' analysis that illegal tin mining activities in East Belitung Regency continue to be caused by factors of actors who support and provide facilities and sales channels. In addition, the relationship between actors that create an interdependent network causes illegal tin mining practices to persist. Actors involved in illegal tin mining relations in East Belitung Regency include state actors, main actors (community, and supporting actors (private). Each actor has a role and influence that is mutually binding between one actor and another which causes dependence between one and another to be strong. The high dependence between these actors then complicates the process of cracking down on illegal tin mining, thus implicating the difficulty of eradicating illegal tin mining in East Belitung Regency